2019
DOI: 10.22336/rjo.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR C677T and A1298C Polymorphisms with Glaucoma Risk: a Systematic Review Meta-Analysis based 42 Case-Control Studies

Abstract: Aim: Several epidemiological studies have been performed to explore the association of MTHFR polymorphisms with glaucoma risk. However, the results were inconsistent or even inconclusive. Hence, we performed a meta-analysis to evaluate the association of MTHFR C677T and A1298C polymorphisms with glaucoma risk. Methods: A comprehensive literature search on PubMed, Google Scholar, EMBASE, and CNKI databases was performed to find all eligible studies up to January 30, 2019. The pooled odds ratios (ORs) with 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There are studies implying that genetic polymorphism, such as variant MTHFR A1298C, may increase the risk for developing glaucoma, especially in the heterozygote model [ 9 , 22 ]. However, in order to support this idea, extended studies are still necessary [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies implying that genetic polymorphism, such as variant MTHFR A1298C, may increase the risk for developing glaucoma, especially in the heterozygote model [ 9 , 22 ]. However, in order to support this idea, extended studies are still necessary [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary glaucoma is classified in primary open angle glaucoma (POAG), primary congenital glaucoma (PCG) and primary angle-closure glaucoma (PACG). There are several studies that support that genetic polymorphism, such as the variant MTHFR A1298C, may increase the risk for developing glaucoma, especially in the heterozygote model [ 9 , 22 ]. However, while there are meta-analyses supporting this idea, other studies are yet to be extended, given the fact that, while some of these studies tried to maintain a heterogeneity of the assessed patients, other studies were made on specific ethnic groups [ 7 ].…”
Section: Considerations On Genetical Factors Linking Glaucoma Associa...mentioning
confidence: 99%
See 1 more Smart Citation
“…We found some problems when reviewing previous literatures. For example, Gohari et al [33] , based on 33 studies with 3504 glaucoma patients and 2525 controls, offered different opinion on the MTHFR C677T susceptibility with glaucoma (containing POAG patients). We found they might miscalculate the frequency of TC genotype and misclassified the source of control from hospital-based group into the community-based ones [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Because photoreceptors initiate visual transduction, their absence could result in the death of RGCs due to the lack of stimulation earlier in the pathway. Moreover, because homocysteine metabolism occurs in every cell, its defective metabolism within both the RGCs and optic nerve can be another possibility behind the mechanism of HHcy-associated POAG [ 127 , 128 ]. In fact, a functional analysis of the mthfr mutant mice demonstrated that HHcy in the retina of mice led to increased RGC death [ 129 ].…”
Section: The Pathophysiology Of Homocysteine In Primary Open Angle Gl...mentioning
confidence: 99%